2018
DOI: 10.1093/ntr/nty184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Randomized Clinical Trial Comparing the Effectiveness of a Culturally Targeted and Nontargeted Smoking Cessation Intervention for Lesbian, Gay, Bisexual, and Transgender Smokers

Abstract: Study results have implications for understanding the benefits of culturally targeted compared to non-targeted smoking cessation interventions for improving smoking cessation outcomes among LGBT smokers. Short and longer-term 7-day point prevalence quit rates associated with the targeted and non-targeted interventions were modest but comparable to other group based interventions delivered in a community setting. Although cultural targeting improved the overall acceptability of the intervention, no added benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…36 After adjustment for LOT-R and income, print group was found to be associated with SC among Puerto Rican individuals (P = .032), such that culturally targeted print materials were associated with lower SC rates compared with standard CDC print materials (OR, 0.75; 95% CI, 0.07-0.85).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…36 After adjustment for LOT-R and income, print group was found to be associated with SC among Puerto Rican individuals (P = .032), such that culturally targeted print materials were associated with lower SC rates compared with standard CDC print materials (OR, 0.75; 95% CI, 0.07-0.85).…”
Section: Discussionmentioning
confidence: 98%
“…These findings differ from those of cancer prevention and control studies that examined the effect of culturally targeted interventions in diverse populations, which found that compared with standard approaches, cultural targeting resulted in more positive evaluations and greater acceptability of cancer prevention interventions. 36…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, evidence for the superiority of SGM-tailored interventions over nontailored interventions is inconsistent. 10 In trials of smoking cessation programs tailored to gay men 11,12 and to the broader SGM community, [13][14][15] abstinence rates were comparable to those of non-SGM tailored smoking cessation treatments in the United States 16 and the United Kingdom. 17 These earlier evaluations were of programs that involved face-to-face sessions, which young adult smokers rarely utilize.…”
Section: Introductionmentioning
confidence: 97%
“…21 Importantly, most previous studies did not include a comparison group. Only one study 15 compared tailored and non-tailored interventions. Significant differences were not found; however, the tailored intervention was perceived more positively.…”
Section: Introductionmentioning
confidence: 99%
“…resources to their patients. Although having benefit, prior approaches developed by this established collaborative team at HBH have required high staffing rates, relied on patients being actively in treatment or being willing to come for intensive individual or group treatment sessions [41][42][43]. If effective, this proactive approach being developed in collaboration with HBH offers substantial benefits for the organization and the patient population in terms of reach, cost effectiveness, and increasing access to culturally appropriate services.…”
mentioning
confidence: 99%